TOMAJO people counter counting people through video surveillance - Hisole, Jose Paulo C.
TOMAJO People Counter is a video monitoring system that counts the people going in and out of monitored areas. Mounted surveillance cameras and not overhead cameras are used so that more information such as profiles can be derived from the video. It accepts as input a video file and outputs a bidirectional count of human traffic caught on the video. It is composed of two modules: People Detection and People Counting Module. The People Detection module takes care of the classifying people blobs to non-people blobs. Mixture of Gaussian and Connected Components algorithm as well as noise reduction techniques such as dilation and size constraints are used in this module. The People Counting module takes care of the bidirectional count by tracking each blob using the blob's centroid as well as their size. The frame is partitioned into 2 regions and the count in and out are deduced from analysing the blob's motion through these regions. For testing purposes, we implemented the system on footages taken from the entrance hall of the UP Alumni Engineers Centennial Hall. The application gives 100% precision and 76% recall for simple cases that doesn't have occlusion. However, false negatives are more observed when there is occlusion in the footages giving 96% precision and 33% recall.